A highly selective surface coating for enhanced membrane rejection of endocrine disrupting compounds: Mechanistic insights and implications. (15th September 2017) - Guo, Hao; Deng, Yu; Yao, Zhikan; Yang, Zhe; Wang, Jianqiang; Lin, Chuner; Zhang, Tong; Zhu, Baoku; Tang, Chuyang Y.
Abstract: We designed a highly selective surface coating to achieve enhanced rejection of endocrine disrupting compounds (EDCs) by nanofiltration membranes. A commercial NF90 membrane was first coated with polydopamine (PDA) followed by in situ immobilization of silver nanoparticles (AgNPs). This PDA/AgNPs coating greatly improved EDC rejection at the expense of slight water permeability loss (4–10%). This improvement in rejection can be attributed to a combination of enhanced size exclusion and suppressed hydrophobic interaction. A resistance-in-series analysis further reveals that the coating was highly permeable to water but highly resistant to EDCs, leading to an EDC selectivity that was an order of magnitude greater than those of the bare PDA coating and the base membrane NF90. The current study provides important insights into the design of highly selective coatings for effective retention of targeted trace organic contaminants. Graphical abstract: Highlights: A highly selective silver/polydopamine coating was applied to an NF membrane. The coating greatly enhanced the rejection of endocrine disrupting compounds (EDCs). Water permeability loss of the coated membrane was <10%. The coating could enhance the effect of size exclusion and surface hydrophilicity. The coating was highly permeable to water and highly resistant to EDCs.